Does the Sermon on the Mount include an ecological message? - Marian Machinek (Nova Prisutnost, 2020)
The purpose of this article is to examine whether the Sermon on the Mount (Matt 5–7) can be an inspiration for ecological spirituality. Jesus’ diagnosis of the human attitude (Matt 6:19–34), marked by an immoderate desire to possess and by excessive concern for the future, has not lost anything in its relevance. Changing this attitude might be possible through a renewed look at surrounding nature. The relationship to God will be a key element of Christian ecological spirituality.